The Military Code of Utah, ch. 53, § 53, 1894 Utah Laws 64, 76-77. - (:unkn) unknown (My University, 1894)
It shall not be lawful for any body of men whatever, other than the regular organized vol§unteer militia of this Territory, and the troops of the United States, to associate themselves together as a military company or organization, or to drill or parade with arms in any city or town of this Territory
Keywords: MILITIAS